Pemodelan Kondisi Geometrik Jalan Terhadap Potensi Kecelakaan Lalu Lintas - Yogi Oktopianto; Riza Pahlevi Marwanto; Rukman Rukman (Borneo Engineering : Jurnal Teknik Sipil, 2023)
Road infrastructure has an impact on the occurrence of road traffic accidents. The geometry of a road is a variable that influences the occurrence of road traffic accidents. Interpreting the observed crashes into an equation that can describe the crashes is one of the most difficult problems faced by scientists and engineers in any research. The traffic accident research conducted is still limited to analyzing the causes of accidents and jumping to handling strategies that do not reveal how much geometric influence on accidents at the location. This research was developed using a comprehensive modeling approach to illustrate how highway geometric design, in this case the alignment, influences crash rates. This study aims to analyze the influence of road geometrics on the incidence of accidents. The method used is multiple liner regression measurement model using R-Studio. The variables to be studied include road geometry planning parameters, especially horizontal alignments which include stopping sight distance (X1), radius of horizontal curve (X2), shoulder width X3, and transition curve length (X4). The results of the study obtained a relationship in the mathematical equation Y = 99.55508-0.02634X1+1.17647X2-0.06999X3-0.03906X4 with the most significant correlation value produced is the transition curve length and radius of horizontal curve. Based on the multiple R-squareed value of 0.8775 this model has a very strong correlation category. Where the ability of X1 to X4 is able to explain Y by 80%.